Role of Lymphopenia in Early prediction of Infection Following Orthotopic Liver Transplantation in Cirrhotic Patients - Mikhael Giabicani; Mikhael Giabicani; Clara Timsit; Léa Copelovici; Pauline Devauchelle; Marion Guillouët; Marina Hachouf; Sylvie Janny; Juliette Kavafyan; Stéphanie Sigaut; Tristan Thibault-Sogorb; Safi Dokmak; et al. (Transplant International)
Infections remain a main cause of morbidity and mortality following orthotopic liver transplantation (OLT). Patients with end-stage liver cirrhosis exhibit a deregulation of their immune response, making them more susceptible to infections. From a prospective database, we retrospectively assessed the ability of preoperative lymphopenia, as a marker of this immune dysregulation, to predict the occurrence of early postoperative bacterial infections during post-OLT ICU hospitalization in patients with cirrhosis. Between January 2011 and December 2021, we included 445 patients. Post-OLT infections occurred in 92 patients (21%) and were mainly represented by bacteriemia (39%), pneumonia (37%) and surgical site infection (30%). Preoperative lymphocyte count ≤1.150 × 109/L was identified as an independent risk factor, as well as preoperative encephalopathy, intraoperative RBC transfusion >2 and intraoperative maximum norepinephrine dose >0.5  μg.kg−1.min−1 (all p < 0.05). Bootstrap analysis validated these results (p < 0.05). The risk factors were integrated into the PRELINFO score which was associated with the risk of infection (p < 0.05). The depth of preoperative lymphopenia was also associated with the risk of infection and postoperative correction of lymphopenia was slower in patients who developed an infection than in those who did not. Preoperative blood lymphocyte count should be incorporated into the assessment of the risk of early post-OLT bacterial infections.